Improving students’ vocabulary learning using finding word games: a classroom action research - Totti, Christian; Kurniawati, Tri; Darajat, Ageung; Wathoni, Hamzani (Mell Baou Publisher, 2024)
This study aimed to enhance eighth-grade students' vocabulary acquisition using Finding Word Games, employing a Classroom Action Research approach. Data was collected using observation sheets and vocabulary tests and analyzed with content analysis and measurement techniques. The study was conducted with 20 students (11 male and 9 female) in Class VIII C at SMP Santa Monika, Kubu Raya, West Kalimantan. In the first cycle, the average vocabulary test score was 65.4, with a 10% completion rate, and the highest score was 78. By the second cycle, the average score improved to 77.1, with an 80% completion rate, and a peak score of 85. This represented an 11.7-point increase in average scores and a 70% improvement in completion rates between cycles. Findings suggest that the integration of Finding Word Games as an instructional tool can significantly improve students' vocabulary learning, offering an engaging and effective method for vocabulary instruction.